2009
DOI: 10.1194/jlr.m900040-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Surface study of apoB1694–1880, a sequence that can anchor apoB to lipoproteins and make it nonexchangeable

Abstract: Apolipoprotein B (apoB) is a nonexchangeable apolipoprotein. During lipoprotein assembly, it recruits phospholipids and triacylglycerols (TAG) into TAG-rich lipoprotein particles. It remains bound to secreted lipoproteins during lipid metabolism in plasma. The b1 region (residues 827-1880) of apoB has a high amphipathic b strand (AbS) content and is proposed to be one region anchoring apoB to lipoproteins. The AbS-rich region between apoB37 and apoB41 (residues 1694-1880) was cloned, expressed, and purified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
6
18
1
Order By: Relevance
“…This observation supports the notion that apo-B100 in VLDL is loosely packed at the interface covering a large surface area with low interfacial surface tension [59]. During particle conversion from VLDL to LDL, however, the relative number of surface molecules increases and a higher molecular packing density leads to a compression of the lipid anchored protein regions and an overall stiffening of the LDL particle [60]. To conclude, the intrinsic conformational flexibility and elasticity of apo-B100 containing lipoprotein particles is most likely critical for specific affinities of lipoproteins to receptors, antibodies or enzymes.…”
Section: Apo-b100 Containing Lipoproteins Are Very Soft and Flexiblesupporting
confidence: 76%
See 1 more Smart Citation
“…This observation supports the notion that apo-B100 in VLDL is loosely packed at the interface covering a large surface area with low interfacial surface tension [59]. During particle conversion from VLDL to LDL, however, the relative number of surface molecules increases and a higher molecular packing density leads to a compression of the lipid anchored protein regions and an overall stiffening of the LDL particle [60]. To conclude, the intrinsic conformational flexibility and elasticity of apo-B100 containing lipoprotein particles is most likely critical for specific affinities of lipoproteins to receptors, antibodies or enzymes.…”
Section: Apo-b100 Containing Lipoproteins Are Very Soft and Flexiblesupporting
confidence: 76%
“…However, to evaluate lipid-protein interactions physical parameter like interfacial elasticity or molecular dynamics have to be considered. In this context, it was suggested that the hydrophobic -sheet domains of apo-B100 act as elastic lipid anchors, whereas the amphipathic -helical domains respond rapidly to changes in surface pressure [59,60]. In any case, it can be assumed that alterations in the adsorption and penetration depth of apo-B100 in the phospholipid monolayer and in the lipid core are accompanied by structural rearrangements of the domains and changes in the orientation of the domains relative to each other.…”
Section: Apo-b100 Is a Flexible String Wrapped Around The Surface Of Ldlmentioning
confidence: 99%
“…Some relief from high pressure will occur as albumin removes fatty acids and perhaps 2-monoacylglycerol from the interface. Note that apoB is irreversibly bound to CM and VLDL by its amphipathic ␤ strand domains ( 60 ), whereas its other loosely bound domains can desorb, thus decreasing the area covered by apoB ( 62 ). These detached domains probably have an altered conformation and perhaps change their ligand binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…We have been using a novel surface chemistry technique, oil-drop tensiometry, to study the pressure-mediated adsorption, desorption, and fl exibility behavior of apolipoproteins, their segments, and consensus peptides at physiologically relevant model lipoprotein surfaces ( 38,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62), such as triolein/water (TO/W) and phosphatidylcholine/triolein/water (POPC/TO/W) interfaces. Our novel technique provides a unique point of view to look at the interaction between apolipoproteins and lipids.…”
mentioning
confidence: 99%
“…During biogenesis, a portion of the nascent apoB-100 may exist in an intermediate, uncommitted state: not fully secretion-competent, yet not terminally malfolded. ApoB-100 contains hydrophobic b domains that bind strongly to lipids ( 27 ). Until the quality control surveillance machinery is satisfi ed with the status of these domains, it appears that apoB-100 must remain accountable to the ERAD pathway.…”
Section: Discussionmentioning
confidence: 99%